DESAIN DAN IMPLEMENTASI PADA CUSTOMER CARE SRVICE MOBIL PT ASTRA DAIHATSU MALANG - Ariansyah, Enggar Silvia; Andoko, Banni Satrio; Primandari, Liduina Asih (DINAMIKA DOTCOM, 2015)
PT Astra Daihatsu is one of private companiesâs leading in Indonesia. The company is obliged to have a forge with a good service center. But, customers do not statisfied with the service because the officers service forget not doing confirmation that a car is completed. This is because the absence of system automatically confirmation that can be done directly from step position a car services.The destiny of this research is make the application of sms a gateway on customer care service the car and for comparison with the system and nothing of a system. A method of research selected is a method of collecting data and System Development Life Cycle. A method of collecting data such as observation, the study of pustaka, and the spread of kuisioner performed at a research. Survey have done for customers after the system finished. A method of analysis system development begins system existing and to be developed, and then design of making, and finally do our tests at a system that will be made on the research. The result of the study can facilitate its employees and customers who does not reside in the service center. Beside that the customers also receive sms notice of a systems that a vehicle is completed without the customers calling the service center. Keywords : SMS Gateway, Service